RF-dressed Rydberg atoms in hollow-core fibres - Veit, C; Epple, G; Kübler, H; Euser, Tijmen; Russell, P St J; Löw, R (Institute of Physics, 2019)
The giant electro-optical response of Rydberg atoms manifests itself in the emergence of sidebands in the Rydberg excitation spectrum if the atom is exposed to a radio-frequency (RF) electric field. Here we report on the study of RF-dressed Rydberg atoms inside hollow-core photonic crystal fibres (HC-PCF), a system that enables the use of low modulation voltages and offers the prospect of miniaturised vapour-based electro-optical devices. Narrow spectroscopic features caused by the RF field are observed for modulation frequencies up to 500 MHz.